Honey Ants (Genus Myrmecocystus) Macroecology: Effect of Spatial Patterns on the Relationship between Worker Body Size and Geographic Range Size - Felizola Diniz-Filho, José Alexandre; Fowler, Harold Gordon [UNESP] (My University, 1998)
Macroecology evaluates the partitioning of physical space and resources among organisms through correlation among ecological variables, such as geographical range size and shape, body size, and population density, measured at large geographical and taxonomic scales. In this article, we analyzed the spatial patterns in worker body size and geographic range size for the 27 described species of honey ants, genus Myrmecocystus Wesmael, in the United States and Mexico, and especially the relationship between these 2 variables after statistically removing their spatial patterns. The 2 variables are correlated, but also displayed significant spatial patterns, as detected by trend surface and spatial autocorrelation analyses. After removing these spatial effects, worker body size and geographic range size were still positively correlated. The relationship, therefore, is not a consequence of spatial effects and it does follow Brown's model, which predicts that the geographic range size will have a positive slope on body size. In this model, the lower population densities caused by foraging activities and local territorial competition are associated with a large geographic range, avoiding stochastic extinction. Although this constraint in local population density does not necessarily hold for small organisms such as insects that could achieve high densities even in very small areas and patchy habitats, it may hold for social insects, especially ants, because of the local competition among colonies.
Keywords: Body size; Geographic range; Honey ants; Macroecology; Myrmecocystus; Trend surfaces